Pemenuhan Spiritual Pada Pasien Kanker : A Literature Review - Marti Husen; Iman Permana (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2021)
Background: Cancer treatment can not only focus on the quantity or physicality of the patient, but also pay attention to factors of quality of life, pain, stress, anxiety, fatigue, fear of death, and depression in patients who are often missed in the treatment of cancer patients. Spiritual needs are important needs to be met in patients with cancer in addition to other aspects of the need, because this disease can affect all aspects of the sufferer's life both physical, psychological and spiritual. Objective:this study aims to determine the spiritual fulfillment in cancer patients. Method : This research is a literature review with the process of collecting data through 3 databases namely Pubmed , EBSCO and Proquest . Search Literature with the word key